Correlation between Percentage of Reticulated Platelets and Heart Score in Patients with Suspected Non-ST Elevation Acute Coronary Syndromes - Fransisca Mulyadi; Delita Prihatni; Coriejati Rita; Dewi Kartika Turbawaty; Astri Astuti (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Thrombus formation in non-ST Elevation Acute Coronary Syndrome (NSTE-ACS) causes increased platelet consumption, leading to a 20-fold increase of Reticulated Platelets (RP) release. Reticulated platelets have more granules and proteins that make them quickly forming thrombus than mature platelets, potent to form bigger thrombus, and increase the risk of Major Adverse Cardiac Events (MACE). HEART score is a risk stratification for possible NSTE-ACS, which can predict MACE. The study aimed to analyze the correlation between the percentage of reticulated platelets and HEART score. This research was a correlation observational cross-sectional study performed in Dr. Hasan Sadikin Hospital, Bandung, from August 2018 to May 2019. The subjects were patients suspected with NSTE-ACS by clinicians in the Emergency Department of Dr. Hasan Sadikin Hospital. These subjects were assessed for the HEART score and RP percentage. This study involved 52 subjects consisting of a higher number of males (76.9%) aged 45-64 years old (69.2%). HEART score stratification in this study was mostly high risk (69.2%), but none was low risk. Mean of platelet count, absolute 3 3 RP, and RP percentage were 271±73 x103/mm , 9.3±4.3 x 103/mm , and 3.6±1.7%, respectively. The correlation test between RP percentage and HEART score with a 95% confidence interval using Spearman's correlation test showed a significant positive correlation with moderate strength (p < 0.001 and r=0.475). The percentage of RP in this study was in the normal range. However, there was a significant positive correlation with moderate strength between the percentage of RP and HEART scores in patients with suspected non-ST elevation acute coronary syndrome.